Molecular Cloning, mRNA Expression, and Localization of the G-protein Subunit Galphaq in Sheep Testis and Epididymis - Li, Zhen (Asian-Australasian journal of animal sciences, 2016)
The reproductive function of G-protein subunit Galphaq (GNAQ), a member of the G protein alpha subunit family, has been extensively studied in humans and rats. However, no data is available on its status in ruminants. The objectives of this study were to evaluate the expression pattern of the GNAQ in the testis and epididymis of sheep by polymerase chain reaction (PCR). The mRNA expression levels were detected by real-time fluorescent quantitative PCR, and cellular localization of GNAQ in the testis and epididymis was examined by immunohistochemistry. Additionally, GNAQ protein was qualitatively evaluated via western blot, with the results indicating that similarities between GNAQ mRNA levels from sheep was highly conserved with those observed in Bos taurus and Sus scrofa. Our results also indicated that GNAQ exists in the caput and cauda epididymis of sheep, while GNAQ in the testis and epididymis was localized to Leydig cells, spermatogonial stem cells, spermatocytes, Sertoli cells, spermatid, principal cells, and epididymis interstitial cells. The concentrations of GNAQ mRNA and protein in the caput and cauda epididymis were significantly greater than those observed in the corpus epididymis (p<0.01) and testis (p<0.05). Our results indicated that GNAQ exists at high concentrations in the caput and cauda epididymis of sheep, suggesting that GNAQ may play an important role in gonad development and sperm maturation